Yield and Safety of Transjugular Versus Percutaneous Liver Biopsies in Suspected Cases of Diffuse Liver Disease and Correlation of Yield of Transjugular Liver Biopsy with Hepatic Venous Pressure Gradient - Mousam Dey; Simi Das; Argha Chatterjee; Agnibha Dutta; Ranajoy Ghosh; Jayanta Dasgupta (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Background Liver biopsy is indicated in both diagnosis and prognosis of diffuse liver diseases. Conventionally, percutaneous liver biopsy (PLB) is used, as it is easily available, affordable and has a shorter procedure time, whereas transjugular liver biopsy (TJLB) is used in the setting of ascites and coagulopathy. Our aim is to evaluate the diagnostic yield of TJLB in comparison to PLB with tract embolization. Our secondary aims were to evaluate whether there is any difference in rate of major and minor complications between the two procedures and evaluate whether there is any correlation between diagnostic yield of TJLB and hepatic venous pressure gradient (HVPG). Methods In this retrospective study, we included a total of consecutive 123 patients who underwent liver biopsy through percutaneous (n = 97) and transjugular route (n = 26). We compared the yield of the specimen based on the number of complete portal tracts (CPT). Results There was no significant difference between mean CPT in TJLB and PLB specimens (mean CPT of TJLB and PLB were 10.9 ± 2.7 and 11.6 ±2.5, respectively [p = 0.566]). There was a moderate but significant negative correlation between the total number of CPT and HVPG in the TJLB group (Spearman's rho − 0.58) (p = 0.002). There was no statistically significant difference in minor complication between the two procedures. Only one patient who underwent PLB developed major complication and none of TLJB procedure had any major complication. Conclusion Yield of tissue and complication rates are comparable in TJLB and PLB groups. Yield of tissue in TJLB have intermediate but significant negative correlation with HVPG.